Variability in Eggplant (Solanum melongena L.) and Its Nearest Wild Species as Revealed by Polyacrylamide Gel Electrophoresis of Seed Protein - Hasan, Sayed M. Zain; Isa, Mimi Linda (Universiti Putra Malaysia Press, 1998)
A study was undertaken to determine and distinguish the genotypes of eggplant (Solanum melongena L.) and its nearest wild species by sodium dodecylsulphate polyacrylamide gel electrophoresis (SDS-PAGE) of soluble seed proteins. Fifty four accessions of cultivated and wild groups of eggplant were subjected to the analysis. The results of electrophoretic banding patterns show that there was a great deal of variation within and between groups of eggplant in terms of numbers, sizes, positions, staining intensities and presence or absence of protein bands in the profile, which can be used for characterization and identification of eggplant cultivars. Elongated fruit eggplant cultivars exhibited nine common group-specific bands which distinguish them from the other groups. Meanwhile, a great variability in seed protein profiles was detected in the round fruit type and primitive cultivars, weedy and wild groups of egg plant including the truly wild S. incanum, which indicated that these groups consist of diverse genotypes.